The potential of Andaliman (Zanthoxylum acanthopodium DC) fruit as an ethanol extract for neuroprotection in aged model rat - Anggraini, Dwi R; Ilyas, Syafruddin; Hasibuan, Poppy A Z; Machrina, Yetty; Widyawati, Tri; Rusdiana, Rusdiana; Lumongga, Fitriani; Mustika, Suryani E (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: Dementia is a common aging-related neurodegenerative disease in the elderly worldwide. Alterations in neurogenesis and angiogenesis factors have been linked to cognitive impairment in neurological disorders. However, synthetic drugs to improve memory disorders have uncomfortable side effects. The purpose of this study is to explore the neuroprotective potential of the fruit ethanol extract of andaliman (Zanthoxylum acanthopodium DC) [Andaliman fruit ethanol extract (AEE)] on brain-derived neurotrophic factor (BDNF), vascular endothelial growth factor (VEGF), and spatial memory in rat models of aging. Materials and Methods: This study had an experimental design with AEE. The 4 groups were treated as follows: N (normal), M (served as positive control), P1 (AEE 150 mg/kg bw), and P2 (AEE 300 mg/kg BW) for 8 weeks. Aged model rats (M, P1, and P2) were obtained by inducing D-galactose (150 mg/kg bw). BDNF and VEGF expression were determined by RT-PCR, and spatial memory was assessed using the test of the Moris Water Maze (MWM). The Kruskal–Wallis and Mann–Whitney tests were used to assess the statistical analysis. Results: AEE had a tendency to increase BDNF in P2 compared to the normal group (1.98 versus 1). VEGF expression increased in P1 and P2 compared to the normal group (1.14 and 1.29 versus 1). AEE at a dose of 300 mg/kg bw significantly improved spatial memory (p = 0.026). Conclusion: For eight weeks, AEE at a dose of 300 mg/kg bw considerably increased the potential to enhance VEGF and BDNF expression as well as spatial memory. J. Adv. Vet. Anim. Res., 10(4): 587–592, December 2023 http://doi.org/10.5455/javar.2023.j713